Cutaneous manifestations in patients with mastocytosis: consensus report of the European Competence Network on Mastocytosis; the American Academy of Allergy, Asthma and Immunology; and the European Academy of Allergology and Clinical Immunology - Hartmann, Karin; Reiter, Andreas (The journal of allergy and clinical immunology, 2016)
Cutaneous lesions in patients with mastocytosis are highly heterogeneous and encompass localized and disseminated forms. Although a classification and criteria for cutaneous mastocytosis (CM) have been proposed, there remains a need to better define subforms of cutaneous manifestations in patients with mastocytosis. To address this unmet need, an international task force involving experts from different organizations (including the European Competence Network on Mastocytosis; the American Academy of Allergy, Asthma & Immunology; and the European Academy of Allergology and Clinical Immunology) met several times between 2010 and 2014 to discuss the classification and criteria for diagnosis of cutaneous manifestations in patients with mastocytosis. This article provides the major outcomes of these meetings and a proposal for a revised definition and criteria. In particular, we recommend that the typical maculopapular cutaneous lesions (urticaria pigmentosa) should be subdivided into 2 variants, namely a monomorphic variant with small maculopapular lesions, which is typically seen in adult patients, and a polymorphic variant with larger lesions of variable size and shape, which is typically seen in pediatric patients. Clinical observations suggest that the monomorphic variant, if it develops in children, often persists into adulthood, whereas the polymorphic variant may resolve around puberty. This delineation might have important prognostic implications, and its implementation in diagnostic algorithms and future mastocytosis classifications is recommended. Refinements are also suggested for the diagnostic criteria of CM, removal of telangiectasia macularis eruptiva perstans from the current classification of CM, and removal of the adjunct solitary from the term solitary mastocytoma.